Sympathetic enhancement in futsal players but not in football players after repeated sprint ability test - Chen, Yung-Sheng (BMJ Open Sport Exerc Med, 2015)
BACKGROUND: Heart rate variability (HRV) can disclose the specific adaptation of sympathovagal modulation to exercise. This study investigated the change in HRV measures after anaerobic and aerobic intermittent exercises in university football and futsal players. METHOD: 36 male university students with physically active lifestyle (n=14), football (n=12), and futsal (n=10) participated in this study. The participants completed the repeated sprint ability (RSA) test and Yo-Yo (YY) intermittent recovery test level 1 in randomised order. ECG signals of the participants were recorded in supine position 15 min before and 30 min after exercises. Before exercise, and 5 and 30 min after exercise, the blood pressures were also taken. RESULTS: In the RSA protocol, the percentage changes in normalised high-frequency power (nHFP) were significantly decreased, while the percentage changes in the very low/high frequency power ratio (VLHR) and low/high frequency power ratio (LHR) were significantly increased in futsal players after exercise, as compared with the controls. No significant changes in all HRV indices were found in the YY protocol, except the respiratory frequency. CONCLUSIONS: After exercise, the percent decrease in vagal modulation in futsal players was significantly reduced, while the percentage increase in sympathetic modulation in futsal players was significantly enhanced in the RSA test, but not in the YY test, as compared with the control group. The increase in sympathetic activity and the decrease in vagal activity in the futsal players were greater than the corresponding increase and decrease in the football players in the RSA test.